On Othello and Desdemona - Kottman, Paul (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2018)
Kottman argues, against Stanley Cavell’s reading of Othello, that Othello’s murder of Desdemona stems from his need to demonstrate Desdemona’s independent desire and autonomy – rather than, as Cavell has it, to “avoid” or “deny” that independent vitality. Othello would rather see Desdemona dead at his feet than bent before him on her knees; his own freedom (as he understands it) depends upon Desdemona’s freedom, on her not being merely obedient. Kottman also argues that Desdemona herself plays a role in her own undoing; by risking her life to make love to Othello, she gives him the right to destroy her. Under the circumstances, it is the only action she can make sense of as her own. Keywords: Sexual love, Freedom, Stanley Cavell, Skepticism, Othello, Jealousy